2023
DOI: 10.1094/pdis-02-22-0448-fe
|View full text |Cite
|
Sign up to set email alerts
|

IDphy: An International Online Resource for Molecular and Morphological Identification of Phytophthora

Abstract: Phytophthora, with 203 species, is a genus of high importance in agriculture worldwide. Here we present the online resource "IDphy" (Link) developed to facilitate the correct identification of species of Phytophthora using the type specimens from the original descriptions wherever possible. IDphy emphasizes species of high economic impact and regulatory concern for the United States. IDphy presents an interactive Lucid key and a tabular key for 161 culturable species described as of May 2018, including 141 ex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…castanetorum , thus allowing for a more detailed resolution of clade 12 ( Fig 3 ). This clade was previously referred to as 3b [ 16 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…castanetorum , thus allowing for a more detailed resolution of clade 12 ( Fig 3 ). This clade was previously referred to as 3b [ 16 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…castanetorum , have been described. By incorporating these new sister species and using a multilocus approach, it has been confirmed that these four species comprise a new clade 12 [ 13 , 16 , 63 ]. The phylogeny presented here supports this conclusion, with P .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations